2019
DOI: 10.1021/acs.jpclett.9b00506
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Voltage Losses in CZTSSe Solar Cells of Varying Sn Content

Abstract: The performance of kesterite (Cu2ZnSn(S,Se)4, CZTSSe) solar cells is hindered by low open circuit voltage (Voc). The commonly used metric for Voc-deficit, namely, the difference between the absorber band gap and qVoc, is not well-defined for compositionally complex absorbers like kesterite where the bandgap is hard to determine. Here, nonradiative voltage losses are analyzed by measuring the radiative limit of Voc, using external quantum efficiency (EQE) and electroluminescence (EL) spectra, without relying on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…Non-radiative recombination, which is usually observed in many organic and inorganic solar cells, is, therefore, not considered directly. [24][25][26] When evaluated at the surface, the detailed balance model yields the classical Shockley-Queisser limit with optimum band-gap values between $ 1:1 and $ 1:4 eV and a maximum efficiency of $ 33% (Figure S1A). 14 As surface waves affect the incoming spectrum just below sea level depending on the weather, 3 the generated power density and efficiency of the underwater solar cells were All calculations were performed at 300 K to allow for a direct comparison with the Shockley-Queisser limit.…”
Section: Underwater Solar Cell Efficiency Limitsmentioning
confidence: 99%
“…Non-radiative recombination, which is usually observed in many organic and inorganic solar cells, is, therefore, not considered directly. [24][25][26] When evaluated at the surface, the detailed balance model yields the classical Shockley-Queisser limit with optimum band-gap values between $ 1:1 and $ 1:4 eV and a maximum efficiency of $ 33% (Figure S1A). 14 As surface waves affect the incoming spectrum just below sea level depending on the weather, 3 the generated power density and efficiency of the underwater solar cells were All calculations were performed at 300 K to allow for a direct comparison with the Shockley-Queisser limit.…”
Section: Underwater Solar Cell Efficiency Limitsmentioning
confidence: 99%
“…( V OC,def can be calculated from the bandgap E g and the charge of an electron as EnormalgqVOC, where V OC is obtained from the current density−voltage [ J − V ] analysis under AM 1.5G conditions.) [ 18,19 ] At least in part, large V OC,def is attributed to carrier recombination, [ 20,21 ] which is caused by uncharged or charged defects, [ 22 ] and (or) the coexisting secondary phases in the bulk or interfaces of the absorber layer. [ 23–25 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6] Some of the issues for this challenge are currently under investigation such as front buffer optimization, [7] back contact modification [8] and CZTS interface and bulk defects reduction. [9,10] Moreover, Yan et al [11] has reported a V OC of over 710 mV and an increasing of the efficiency (from 5.5% to 6.6%) for CZTS devices using In 2 S 3 /CdS hybrid buffer. These results show that In 2 S 3 /CdS buffers provide a promising way to boost V OC and efficiency of pure sulfide CZTS solar cells.…”
Section: Introductionmentioning
confidence: 99%